BIOACTIVITY, HEMOLYTIC EFFECT AND ANTIBACTERIAL SCREENING OF METHANOL, ETHANOL AND DICHLOROMETHANE CRUDE EXTRACTS FROM THE FIRE CORALS, Millepora dichotoma AND Millepora platyphylla OF MARSA ALAM, RED SEA, EGYPT - ISMAIL, MOHAMED; RAHMAN, M. AMINUR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Preliminary investigation on crude extracts from two fire coral species, Millepora dichotoma (Md) and Millepora platyphylla (Mp), those found along the Egyptian Red Sea coast of Marsa Alam, were collected for bioactivity screening. The bacterial activity and hemolytic effect of the methanol (MeOH), ethanol (EthOH) and dichloromethane (DCM) crude extracts of Md and Mp coral species were tested for their activity against various bacteria, namely; Klebsiela sp., Escherichia coli, Bacillus cereus and Staphylococcus aureus, while hemolytic effects of the crude extracts were tested on human red blood cells (RBC). The results showed differential effects of all coral crude extracts on the tested bacteria, while no hemolytic signs were detected among all the RBC samples. It is recommended to enhance the crude extracts studies form fire corals species as it could be a challenge to use them in safe medical and pharmaceutical applications.